2020
DOI: 10.1021/acs.jpcc.9b10428
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Double Layer Capacitance of Curved Graphite Electrodes

Abstract: To improve the understanding of the relation between electrode curvature and energy storage mechanisms, a systematic investigation of the correlation between convex and concave electrode surfaces and the differential capacitance of an electrochemical double layer capacitor using molecular dynamics simulations is presented. Each electrode consists of three layers of curved graphene sheets with a convex and concave surface to which the constant potential method was applied. The differential capacitance shows a f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
(69 reference statements)
3
15
2
Order By: Relevance
“…Consequently, the discussion concentrates in the following only on the negative electrode. As previously observed in Seebeck et al [9], number density fluctuations of the imidazole group in the EDL with respect to different applied electric potentials, shown in Fig. S3, correlate to features in the differential capacitance of Fig.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Consequently, the discussion concentrates in the following only on the negative electrode. As previously observed in Seebeck et al [9], number density fluctuations of the imidazole group in the EDL with respect to different applied electric potentials, shown in Fig. S3, correlate to features in the differential capacitance of Fig.…”
supporting
confidence: 83%
“…Such a potential-induced phase transition of the double layer at flat electrodes has also been observed experimentally [28,41,42]. Using CONP simulations, we have previously demonstrated the influence of curved electrodes on the differential capacitance, and found correlations between the electrode curvature and the number densities of the electrolyte components as well as the orientation of the ions [9]. In this work, we employ the histogram reweighting approach to estimate free energies of the electric double layer formation which ultimately allows us to correlate the charge fluctuations with structural changes at the electrode-electrolyte interface.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…A few modeling works have mentioned the effect of curvature over the years. 84,140,[255][256][257] Merlet et al used MD simulation to characterize different sites with various morphology of CDC materials (edge, plane, hollow and pocket) and calculate the degree of confinement of the adsorbed ions. 256 The results showed that at the edge, plane, hollow and pocket sites (with the increased degree of confinement) of CDC samples, the degree of desolvation of anions varies compared to the bulk.…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…The introduction of surface oxide in this intermediate step likely changes the carbon-carbon bonding, such that it is reasonable to assume that this resulted in different pore morphologies and pore walls roughnesses during the vacuum annealing, when surface functional groups-like oxygen-are removed. Indeed, there are hints from molecular dynamics simulations that such differences influence the mesoscopic structure and dynamics of an ionic liquid in carbon nanoconfinement [65][66][67]. Also the broad pore-size distribution is presumably of relevance here, because the QENS methods measure the dynamics averaged over all pores.…”
Section: B Full Quasielastic Spectramentioning
confidence: 99%